Understanding the processes of computational abstraction in children: An exploratory case study - Zúñiga Muñoz, René Fabián; Hurtado Alegría, Julio Ariel; Collazos Ordoñez, Cesar Alberto (I+ T+ C- Research, Technology and Science, 2014)
The development of computational thinking in children provides them skills to deal with problems at school and their daily lives. This kind of training is not part of school contents but in mathematical thinking development, which is closely related. However, there are few rigorous studies of the development of this kind of thinking in children, in order to establish appropriate teaching-learning processes in our setting. The key in computational thinking is abstraction, which makes the development of computational thinking a strategy to understand and solve problems in all areas of knowledge. This article presents the main findings about the processes of computational abstraction that children about 10 and 12, used for the analysis and solution of computational problems using scratch 2.0. A long this study, the case study method was used. In order to explore the phenomenon of abstraction of children in a real learning context. The main result of this study is a set of best practices which should be considered in the teaching and learning process of computational thinking development concerning the aspects of abstraction.